Mapping Leading Plantation Commodities through Comparative and Competitive Advantage Analysis in South Lampung Regency - Rizky Augia; Teguh Endaryanto; Novi Rosanti; Wan Abbas Zakaria (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
This study aims to analyze the structure and economic shifts of the plantation subsector in South Lampung Regency to identify leading commodities. The study uses secondary data from the Central Bureau of Statistics and the Plantation Office of South Lampung Regency. The analysis covers seven plantation commodities spread across 17 subdistricts, comprising a total of 119 observation units. The analytical methods applied include Location Quotient (LQ) and Dynamic Location Quotient (DLQ) to identify base and prospective commodities; Localization Index (LI) and Specialization Index (SI) to assess commodity concentration and subdistrict distincstivness; and Shift Share Analysis (SSA) to evaluate growth, competitiveness, and net shift. The classification of commodity performance at each analytical stage is conducted using the Klassen Typology. The results reveal that 28 commodity–subdistrict units are categorized as base and prospective. Among them, oil palm in Katibung, and cocoa in both Kalianda and Penengahan, are identified as concentrated and distinctive commodities within their respective regions. Moreover, oil palm in Katibung and cocoa in Kalianda are recognized as fast-growing and highly competitive. Notably, oil palm in Katibung records the highest net shift value, positioning it as the leading commodity in the plantation subsector of South Lampung Regency.